Industrial training report: Era Bio Advance (M) Sdn Bhd / Muhammad Faeizwan Jaafar - Jaafar, Muhammad Faeizwan (Perpustakaan Tengku Anis, 2017)
The industrial report is based on the industrial training period from 01 February 2017 to 23 June 2017 at Programmer Department under Era Bio Advance (M) Sdn Bhd. This report entails the experience of mine, the background of organization where I had my practical training and, the industrial training activities I have done throughout the five months period in software development industries. Industrial training is compulsory to all Semester 7 students of Faculty of Information Management, UiTM Machang as it is the partial fulfilment of the requirement in order to be awarded degree in Information Management study. The report of this practical training consist four chapters which are introduction, organization information, Industrial training activities and Conclusions. The main inputs in this report are chapter 3 and chapter 4. Writer will explain in depth activity done within five months here and special project that writer has done. Chapter 4 will cover about knowledge gained, personal opinion, lesson learnt and limitation and suggestion from writer perspective.